Reliable change in cognition over 1 week in community-dwelling older adults: a validation and extension study. (6th February 2020) - Hammers, Dustin B; Suhrie, Kayla R; Dixon, Ava; Porter, Sariah; Duff, Kevin
Abstract: Objective: Reliable change methods can aid neuropsychologists in understanding if performance differences over time represent clinically meaningful change or reflect benefit from practice. The current study sought to externally validate the previously published standardized regression-based (SRB) prediction equations developed by Duff for commonly administered cognitive measures. Method: This study applied Duff's SRB prediction equations to an independent sample of community-dwelling participants with amnestic mild cognitive impairment (MCI) assessed twice over a 1-week period. A comparison of MCI subgroups (e.g., single v. multi domain) on the amount of change observed over 1 week was also examined. Results: Using pairwise t -tests, large and statistically significant improvements were observed on most measures across 1 week. However, the observed follow-up scores were consistently below expectation compared with predictions based on Duff's SRB algorithms. In individual analyses, a greater percentage of MCI participants showed smaller-than-expected practice effects based on normal distributions. In secondary analyses, smaller-than-expected practice effects were observed in participants with worse baseline memory impairment and a greater number of impaired cognitive domains, particularly for measures of executive functioning/speeded processing. Conclusions: These findings help to further support the validity of Duff's 1-week SRB prediction equations in MCI samples and extend previous research by showing incrementally smaller-than-expected benefit from practice for increasingly impaired amnestic MCI subtypes.